The Sociology of Mennonites, Hutterites and Amish : A Bibliography with Annotations, Volume II 1977-1990 - Smucker, Donovan E. (Donovan Ebersole), 1915- (Book collections on Project MUSE., 2018)
The editor provides an important new scholarly tool for locating and understanding the enormous expansion of scholarly research dealing with the sociology of Canadian Mennonites, Hutterites and Amish. Although the book includes research from American scholars, the editor devotes special attention to Canadian works concerning these important and interesting minorities. Using the tripartite division of Mennonites, Hutterites and Amish, the bibliography includes 800 entries each with a concise summary and evaluation. The entries are listed under the subheadings: books, theses, articles and unpublished manuscripts. Preceding the bibliography itself is an essay by the editor originally presented to the Canadian Sociology and Anthropology Association. The essay outlines the differing conceptual assumptions of the researchers included in the book, the major methodologies employed and the main conclusions to be drawn from their work.